Les femmes et l'isolement cellulaire au Canada : un défi de l'esprit sur la matière - Martel, Joane (Canadian journal of criminology and criminal justice, 2006)
Prisons exhibit many of the characteristics of modernity, in which time and space are central preoccupations. This article discusses findings of a recent study on the segregation (solitary confinement) of incarcerated women in Canada. Specifically, it examines the notions of time and space as they are practised by the prison and experienced by women. It argues that operators of time normally used inside the prison (meals, visits, head counts, recreation time, etc.) are de-structured when a prisoner enters segregation cells where she will face a discipline of the temporal minuscule that tends to blur culturally relevant temporal benchmarks that are necessary for the prisoner's reintegration into society. It also argues that prison segregation is a form of spatial confinement that particularly exacerbates the sacredness of personal objects and of housing, which, in turn, impinges on the maintenance of one's habitus as well as of a space necessary for identity formation. (English) [ABSTRACT FROM AUTHOR]